Isolation and molecular characterization of symbiotic fungus from Acromyrmex ambiguus and Acromyrmex heyeri ants of Rio Grande do Sul State, Brazil - Pereira,Daniela Isabel Brayer (2015)
Leaf-cutting ants of the genera Atta and Acromyrmex determine serious agricultural problems and live on symbiosis with Leucoagaricus gongylophorus. The aim of this study is to identify morphological and molecularly, as well as to verify the genotypic variability of the symbiotic fungus cultivated by A. heyeri and A. ambiguus from three different regions of the state of Rio Grande do Sul, Brazil. Fungus gardens were collected and fragments of mycelia were grown in selective medium. Total DNA was extracted and amplification of the ITS region was performed by PCR using universal primers. After DNA sequencing, the chromatograms were assembled and phylogenetic analyzes were performed by the Neighbor-Joining method. A total of six isolates of L. gongylophorus were obtained and their identities were confirmed by molecular analyses. Phylogenetic analysis of the ITS region showed a tree with two distinct groups regarding the fungus isolates from A. heiyeri and A. ambiguous. In this study, it was verified that A. heyeri and A. ambiguous, cultivate the same fungus. Additionally, the molecular marker used in this study showed variations in L. gongylophorus, evidencing two distinct branches in the phylogenetic tree, according to the ant species that cultivate L. gongylophorus. However, other studies involving the inclusion of a great number of isolates of L. gongylophorus, as well as the use of other molecular markers to validate the possible variations in the phylogenetic relationship of this symbiotic fungus are required.